A unique Mycobacterium species isolated from an epizootic of striped bass (Morone saxatilis). - Rhodes, M W (Centers for Disease Control and Prevention, 2001)
We isolated a Mycobacterium sp. resembling Mycobacterium marinum and M. ulcerans from diseased striped bass (Morone saxatilis) during an epizootic of mycobacteriosis in the Chesapeake Bay. This isolate may represent an undescribed Mycobacterium species, based on phenotypic characteristics and comparative 16S rRNA gene sequence.